Pharmacotherapy Outcomes And Cost Evaluation Of Paediatric Epilepsy In Penang Hospital - M. Salih, Muhannad R (2012)
Epilepsy is more common in childhood than in adulthood, and it may have destructive cognitive and social effects. In paediatrics, epilepsy is usually drug resistant because the developmental progressions underlying epilepsy build on signalling elements and cascades that are distinctive to the development of the brain. Thus, epilepsy in children is a particular dilemma that cannot be treated as a subset of adult epilepsy. Numerous issues greatly affect the causation, management and outcome of epilepsy in Asia, including psychosocial, cultural, economic, political, and organisational factors. The general objective of this study was to evaluate the management of paediatric patients with structural-metabolic epilepsy. This included both clinical and economical standpoints in the Out-patient Paediatric Neurology Clinic at Hospital Pulau Pinang, Malaysia. In the first part of this retrospective longitudinal study, an observational clinical evaluation was conducted. The recruited children were followed up for one year after the first visit. The required data were extracted from the medical records. In the second part, an annual prevalence-based economic study was conducted. The total costs of epilepsy management were estimated from the provider (i.e., hospital) perspective, using a bottom-up, microcosting analysis. Medical chart/billing data (i.e., case reports) obtained from the hospital (i.e., provider) were collected to estimate the resources used. In addition, cost-effectiveness analysis was performed to assess the use of therapeutic drug monitoring, and new antiepileptic drugs as add-on therapies in the management of paediatric patients with structural-metabolic epilepsy.